Effects of Rotations With Legume on Soil Functional Microbial Communities Involved in Phosphorus Transformation - Yu, Hui; Wang, Fenghua; Shao, Minmin; Huang, Ling; Xie, Yangyang; Xu, Yuxin; Kong, Lingrang (Frontiers in Microbiology, 2021)
Including legumes in the cereal cropping could improve the crop yield and the uptake of nitrogen (N) and phosphorus (P) of subsequent cereals. The effects of legume-cereal crop rotations on soil microbial community have been studied in recent years, the impact on soil functional genes especially involved in P cycling are raising great concerns. Metagenomic approach was used to investigate the impacts of crop rotation managements of soybean-wheat (SW) and maize-wheat (MW) lasting 2 and 7 years on soil microbial communities and genes involved in P transformation in a field experiment. Results indicated that SW rotation increased the relative abundances of Firmicutes and Bacteroidetes, reduced Actinobacteria, Verrucomicrobia and Chloroflexi compared to MW rotation. gcd, phoR, phoD and ppx predominated in genes involved in P transformation in both rotations. Genes of gcd, ppa, and ugpABCE showed higher abundances in SW rotation than in MW rotation, whereas, gadAC and pstS showed less abundances. Proteobacteria, Acidobacteria and Gemmatimonadetes played predominant roles in microbial P cycling. Our study provides a novel insight into crop P require strategy and help to understand the mechanism of improving crop nutrient uptake and productivity in different rotations.